Marine Pharmacists Safeguard The Health Of People At Sea - Ganesh, Sritheran Paneerselvam; Long, Chiau Ming * (Social Health Analytics Sdn Bhd, 2024)
A licensed marine pharmacist is responsible for conducting comprehensive audits to ensure compliance with industry regulations, safety protocols, and quality standards.